Caracterização tecnológica de rochas ornamentais pegmatíticas do Seridó Oriental Paraibano - Pedra Lavrada/Pb - Leal Neto, Antonio (2017)
The rocks studied are known commercially as Golden Fuji, Fuji White and Fuji Capuccino. They come from the same mining front located in the municipality of Pedra Lavrada/PB. They have a similar mineral composition consisting mainly of quartz, plagioclase, muscovite, microcline and garnet with contents between 5% and 34% and accessory minerals, with contents less than 5%, especially sericite, biotite and opaque. Petrographically correspond to pegmatites with isotropic structure, mineral granulation ranging from medium to very coarse, high degree of mineral microcracking, incipient to moderate mineral alteration and predominant concave-convex mineral contacts. The results obtained in the technological characterization indicate that the investigated pegmatites can be used as ornamental rock, however, reservations regarding the use of White pegmatite are required, as a function of their performance in the technological tests related to physical indices, resistance to uniaxial compression and resistance to values lower than those suggested by current standards. The chemical solutions used affected the initial brightness intensity of the rocks in different proportions: potassium hydroxide caused a loss of 35,6% in the white pegmatite and citric acid induced a loss of brightness of 21,3% and 22,2% %, in the Golden and Capuccino pegmatites, respectively. The results of the colorimetric analysis showed that potassium hydroxide was the chemical reagent responsible for the highest chromatic variation observed in the White pegmatite (ΔE*=7,78) and for the pegmatites Capuccino (ΔE*=8,55) and Golden (ΔE*= 9,18) color changes were caused by the action of citric acid. The values of radon exhalation in the studied rocks are considered high, mainly for the White pegmatite (215,0 Bq/m3), Capuccino (176,3 Bq/m3) and Golden (156,0 Bq/m3). The results for radon gas exhalation efficiency demonstrate that the amount of 222Rn effectively emanated in the rocks is small relative to the total amount of 222Rn generated. The simulation for indoor environments shows that the dosimetric values obtained for White pegmatite were 0,88 pCi/L; 0,73 pCi/L for the Capuccino pegmatite and 0,64 pCi/L for the Golden pegmatite revealing values below the dosimetric limit of 4,0 pCi/L. The results of the study of the thermal conductivity post-etching indicate that there was a reduction in the thermal conductivity values in the pegmatitic types studied (Capuccino: 4,1%, White: 3,4% and Golden: 2,2%) when compared to measurements of the thermal conductivities obtained before the action of the chemical reagents.